Southwest Research-Extension Center, Field Day 2000 (Kansas Agricultural Experiment Station Research Reports, 2000)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 2000; SRP856; crops; tillage; irrigation; insect control; weed science